Penyuluhan Pengelolaan Sampah di Sekolah SMP Muhammadiyah 61 Tanjung Anom - Aguansyah Maulana Siregar; Alwi Ridho; Fauzan Asyqarullah Ginting; Muhammad Syahputra; Natasya Putri Lika; Sri Wahdina Tanjung; Tengku Armita Chairiyah; Nisrina Nisrina (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This community service project aims to overcome the low level of environmental awareness and waste management practices among students at SMP Muhammadiyah 61 Tanjung Selamat. One class showed low levels of cleanliness, with students reluctant to keep the class clean and dispose of rubbish properly. The project conducts educational outreach programs that focus on identifying organic and inorganic waste, emphasizing the importance of proper waste disposal, and the existence of designated disposal sites. Involving a 30-minute session with a pre-test and post-test, this project succeeded in increasing students' understanding of organic and inorganic waste, showing a significant change from the minimal understanding before the intervention. These results emphasize the success of the extension program in increasing students' understanding of waste management, especially in the school environment. Recommendations include implementation of sustainable programs, involvement of parents, collaboration with relevant agencies, and regular monitoring and evaluation to ensure the sustainability of waste management efforts.